Answer:
![(\frac{y}{6 })^{1/4}=f^{-1}(y)](https://tex.z-dn.net/?f=%28%5Cfrac%7By%7D%7B6%20%7D%29%5E%7B1%2F4%7D%3Df%5E%7B-1%7D%28y%29)
Step-by-step explanation:
We have given a function.
f(x) = 6x⁴
We have to find the inverse of the given function.
Putting y=f(x) in given equation ,we have
y = 6x⁴
y/6 = x⁴
Taking 4th root to both sides of Above equation, we have
![(\frac{y}{6})^{1/4}=x](https://tex.z-dn.net/?f=%28%5Cfrac%7By%7D%7B6%7D%29%5E%7B1%2F4%7D%3Dx)
Putting x = f⁻¹(y) in above equation, we have
![(\frac{y}{6 })^{1/4}=f^{-1}(y)](https://tex.z-dn.net/?f=%28%5Cfrac%7By%7D%7B6%20%7D%29%5E%7B1%2F4%7D%3Df%5E%7B-1%7D%28y%29)
Replacing y by x , we have
which is the answer.
f⁻¹(x) is not function because it assigns each value of x to two values of y.
Choice D is correct answer.